Environmental Innovation and Sustainability Practices Manufacturing Companies in Bali Through Government Regulations - DEWI, Kadek Goldina Puteri; KURNIAWAN, Komang Adi; PUTRA, I Wayan Gde Yogiswara Darma (PT Keberlanjutan Strategis Indonesia, 2024)
This study aims to examine the influence of environmental innovation and sustainable practices, and the second objective is to examine the influence of environmental innovation and sustainable practices through government regulations as a moderating variable. This study uses a quantitative approach. This model contains variables that are sought from the literature and are relevant to the study. This study surveyed 413 manufacturing companies in Bali Province. Each statement is a five-point item (i.e., 1-5) asking respondents to agree or disagree with the perception, behavior, or experience specified in the statement. Data processing and analysis were carried out using MRA Analysis Statistical Package for the Social Sciences (SPSS) 22.0.